Thomas Chatterton, the Marvelous Boy : With "The Exhibition," a Personal Satire - Ellinger, Esther Parker (University of Pennsylvania Press, 1930)
A psychological analysis of Chatterton's contradictory mental characteristics, with the first complete publication of his violent verses against the citizens of Bristol.